PROSPECT OF ESSENTIAL OILS DEVELOPED AS BOTANICAL PESTICIDES - SRI YUNI HARTATI (Perspektif, 2012)
Some essential oils exhibit biological activities against microbes, insect pests, as well as vectors pathogens of human, animals, and plants. The properties of essential oils have been exploited and their products have been commercialized and widely used especially in food industries, such as additives and preservatives. Essential oils have a great potential for botanical pesticides, since their biological activities, effectivity, compatibility, target organisms, and environmentally-friendly. Some essential oil-base pesticides have been produced and widely used to control microbial pathogens, insect pests, and vector pathogens in the environment of houses, glass houses, and veteriner. The Minimum Inhibitory Concentration (MIC) of most essential oil-based pesticides are generally low. In the other hand, they are also compatible with other control measures and produce free residues of agricultural products. However, essential oil-base pesticides have some barriers, as well as other botanical pesticides, especially in their stability and effectivity. In addition commercializing essential oil-based pesticides is limited, such as, in the scarcity of the row materials, there is a need for chemical standardization and quality control, and  difficulties in registration. If those barriers and constrains could be solved, essential oils would have a great potential to be developed in commercial scale. The development of essential oil-base pesticides in industrial and commercial scale hopefully would increase farmers income and devisa as well to reduce the use of synthetical pesticides, therefore environmental disasters  would be reduced. Key words: Essential oil, biological activity, microbes, insects, botanical pesticide